THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER SATISFACTION AT JB VAPE STORE - Walewangko, Christ D.; Pangemanan, Sifrid S.; Pandowo, Merinda H. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
As more consumptive and varied behavior of customers in Indonesia and supported with a large population, with cigarette consumption that is high, it is becoming a risk to the country in order to reduce the consumption of cigarettes has a negative impact on health, vape (non-electric) appears and become a suitable alternative to become a substitute product. In the study, the writer only focused on JB vape store because this store is quite popular so it has lots of customers. Realizing that today JB vape had been known by many and having plenty of customers, the level of competition is higher in this line of business. In order to survive in the midst of vape store competition, JB vape must create a consumer-oriented marketing strategy. Several factors that affect customer satisfaction are Product Quality and Service Quality. The results of research conducted through multiple linear regression analysis showed that of the two independent variables product quality and service quality obtained significant results. These results can be caused by consumers assessing the products offered must have a good standard and also for service must be able to compensate for customer standards where the level of consumer satisfaction can make the image of Jb vape store can be considered good.Â Keywords: Product Quality, Service Quality, Customer Satisfaction